THE ENVIRONMENTAL/ECOLOGICAL HUMANITIES IN PERU AND COMPLEXITY - ARCE-ROJAS, Rodrigo (2024)
This article deals with the environmental/ecological Humanities in Peru and its relationship with complexity. For this purpose, a specialized bibliographic search was carried out. The review concludes that although environmental/ ecological humanities are not explicitly developed in Peru to date, there are contributions from the perspective of interdisciplinary and transdisciplinarystudies, especially from literature, the arts, environmental history and forestry philosophy. Some of the hybrid disciplines that are considered components of the environmental/ecological humanities are also developed, although they are not manifestly recognized as contributions towards this field of transdisciplinary studies. The complexity sciences with their orientation of indeterminacy, non-linearity, the study of undecidable and non-trivial problems enriches the understanding of life in general and therefore enriches the framework of contents and action of the environmental/ecological humanities. The environmental/ecological humanities have an important role to play in the face of the challenges of the civilizational crisis and specifically the ecological crisis through the emotional, spiritual, cultural, discursive and action support and mobilization of people and groups for the design and implementation of transitional and regeneration alternatives in terms of transmodernity and complexity.